2017
DOI: 10.1038/s41598-017-02601-7
|View full text |Cite
|
Sign up to set email alerts
|

ApoCIII enrichment in HDL impairs HDL-mediated cholesterol efflux capacity

Abstract: Apolipoprotein CIII (apoCIII) has been reported to be tightly associated with triglyceride metabolism and the susceptibility to coronary artery disease (CAD). Besides, apoCIII has also been found to affect the anti-apoptotic effects of HDL. However, the effect of apoCIII on HDL-mediated cholesterol efflux, the crucial function of HDL, has not been reported. A hospital-based case-control study was conducted to compare the apoCIII distribution in lipoproteins between CAD patients and nonCAD controls and to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 37 publications
4
36
1
Order By: Relevance
“…Cholesterol efflux from macrophages is considered a crucial step of reverse cholesterol transport that is responsible for maintaining normal cholesterol balance. Previous study revealed that RCT had a strong inverse association with carotid intima-media thickness and CAD likelihood independent of HDL-C level [3]. Therefore, cholesterol efflux capacity reflects the global ability of cholesterol efflux from macrophages.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Cholesterol efflux from macrophages is considered a crucial step of reverse cholesterol transport that is responsible for maintaining normal cholesterol balance. Previous study revealed that RCT had a strong inverse association with carotid intima-media thickness and CAD likelihood independent of HDL-C level [3]. Therefore, cholesterol efflux capacity reflects the global ability of cholesterol efflux from macrophages.…”
Section: Discussionmentioning
confidence: 95%
“…After excluding 166 other studies designed as case reports, letters to editor, review articles, in vitro studies, animal studies, 41 articles in full-text article were assessed for eligibility. Finally, 18 articles reporting outcomes of interest were included in the meta-analysis [2,3,7,8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Of them, 12 studies were designed as case-control studies and 6 were cohort studies.…”
Section: Study Selection and Characteristics Of The Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gordon et al 9) and Pamir et al 10) identified several porteins such as apoA1, Gelsolin, antithrombin-III, apoE, and plasminogen as determinants of this capacity. Some proteins including complement C3 9) or apoC3 11) showed negative relationships to cholesterol efflux capacity. However, the relationships have not been consistent among all studies.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that drug-associated larger HDL particles can provide increase amounts of apolipoprotein CIII to the arterial wall. Furthermore, apolipoprotein CIIIenriched HDL particles have been shown to exhibit less functional activity (that is impairment of HDL-mediated cholesterol efflux capacity) (16). It is worth mentioning that increased Apo E levels have been related with ischemic heart disease in men (17).…”
Section: Editorialmentioning
confidence: 99%